Living (RB-stained) benthic foraminiferal fauna sampled along the French Mediterranean coast in 2012 - Briz Parent; Christine Barras; Erica Bicchi; Éric Bénéteau; Laurie M Charrieau; Sophie Quinchard; Frans J Jorissen (PANGAEA, 2021)
The stations were sampled along the French Mediterranean coast in spring (March-April) 2012 onboard the RV Europe. Bottom sediment at 36 stations (between 10 and 71 m water depth) was sampled using a Reineck box-corer. Three replicates (“a”, “b”, “c”; different box-corer launches) were done at each station. Each box-corer was sub-cored with a 7.4 cm diameter tube. Only the first top centimetre was preserved in 96% ethanol and stained with 2 g/L Rose Bengal. At the laboratory, after minimum two weeks each sample was washed through four sieves of 63, 125, 150, and 500 μm mesh sizes. Living (stained) benthic foraminifera from the 125-150 μm and 150-500 μm were collected under stereomicroscope and preserved in micropaleontological slides. Taxonomical recognition was done to the species level. The presented data in the table indicate the raw densities of foraminifera sorted per sample. The exact volume of sampled sediment was measured for each sample.